Intra-household Gender Disparities in Childrens Medical Care before Death in India - Abay Asfaw; Stephan Klasen; Francesca Lamanna (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
The excess female mortality in India and other South Asian countries is no longer contentious. Less known are the reasons for such excess female mortality in the country. In this study, we argue that intra-household gender-discrimination in receipt of medical attention can be one of the most important factors for the unbalanced sex ratio in the country. The 52nd Indian National Sample Survey, which collected for the first time detailed verbal autopsies of deceased persons, is used in the analysis. Place of death, which indicates whether a person get medical help immediately before her/his death, is used as a health indicator variable. The multinomial logit results show that keeping all other factors constant, girls are 1.7 percent less likely to die in hospital than their brothers. The coefficients of different interaction variables also reveal that the probability of infant and very young girls with live female siblings to die in hospital is extremely low. The robustness of the results is also checked using different indicators. The results confirm that girls are highly discriminated in access to hospital treatment and in the number of times being hospitalized before their death compared to boys. Therefore, in addition to the current effort of the government to control sex-selective abortions, efforts should be made to reduce the current intra-household gender-disparities in getting medical care at least for life threatening illnesses.
Keywords: D63; I12; J16; 330; gender discrimination; access to health care; place of death; India